The Literary Portrait from Pushkin to Dostoevsky - Elena V. Stepanian-Rumyantseva (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article explores the peculiarities of literary portraits and studies the interconnections and contrasts between painted and written portraits. The recognizability of a portrait in pictorial art is attained not only through physical resemblance but also through “artistic deformations” that the author introduces to the appearance of the portrayed. In a literary portrait, identification is achieved both by verbal and plastic detailing and by addressing the reader’s inner experience and imagination. Traditionally, the literary portrait in the Russian literature of the 19th century is based mostly on plastic characteristics, comparisons, and color accents, and because of this, it is often defined as “pictorial”. However, portraits by Pushkin and Dostoevsky stand out as exceptionally original, as if created from a different material. Pushkin avoids detailing, instead, he presents a “suggestive” portrait, i.e., a dynamic outline of the personality. The reader’s imagination is influenced not by details, but rather by the dynamic nature of Pushkin’s characters. Dostoevsky does not inherit Pushkin’s methods, though he also turns to a dynamic principle in describing the heroes of his novels. When they first appear, he presents them as if from different angles of vision, and their features may often be in discord, which makes the reader sense a contradictory impact of their personalities, as well as of their portraits. This kind of portrait is a dynamic message, where the reader follows the hero along unexpected and contrasting paths that the author previously mapped for him. From the beginning to the very end of their works, these two classics of Russian literature present the human personality as a being in a state of life-long development, always changing and always free in its existential choice.